PENGARUH PROFITABILITAS, EARNING PER SHARE, LIKUIDITAS DAN LEVERAGE TERHADAP HARGA SAHAM (Studi Pada Perusahaan Sub Sektor Konstruksi Dan Bangunan Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2016) - Mochammad Nur Huda; Sriyono (Research Parks Publishers, 2020)
This study conducted to analyze the effect of variable Return On Asset (ROA), Earning Per Share (EPS), Current Ratio (CR) and Debt To Equity Ratio (DER) to the Stock Prices on company Building Construction Sector Sub companies listed on the Indonesia Stock Exchange period 2012-2016, either partially or simultaneously. The sampling technique used is purposive sampling and number of samples used by 7 companies. Variables used in this study are variable Return On Asset (ROA), Earning Per Share (EPS), Current Ratio (CR) and Debt To Equity Ratio (DER) as an independent and variable Stock Prices as an dependent variable. The analysis technique used panel data analysis. The result showed that Return On Asset (ROA) has negative significant effect on stock prices, Earning Per Share (EPS) has significant effect on stock prices. Current Ratio (CR) has negative significant effect on stock prices. Debt To Equity Ratio (DER) hasn`t significantly effect on stock prices.